2016
DOI: 10.15407/ubj88.01.079
|View full text |Cite
|
Sign up to set email alerts
|

Amine oxidases as important agents of pathological processes of rhabdomyolysis in rats

Abstract: In this study we

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
(22 reference statements)
0
2
0
Order By: Relevance
“…AO is regarded as a biological regulator, especially for cell growth and differentiation ( 44 ). AO is also an important agent of pathological processes of rhabdomyolysis in rats ( 45 ). In mammals, the SPLA2 families are involved in a number of biological processes, such as modification of eicosanoid generation, inflammation, and host defense ( 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…AO is regarded as a biological regulator, especially for cell growth and differentiation ( 44 ). AO is also an important agent of pathological processes of rhabdomyolysis in rats ( 45 ). In mammals, the SPLA2 families are involved in a number of biological processes, such as modification of eicosanoid generation, inflammation, and host defense ( 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…Earlier, we used animal model of rhabdomyolysis, which is accompanied by powerful oxidative stress due to the release of labile ferric iron (Fe 3+ ) from myoglobin/hemoglobin of ruptured myocytes that led to acute kidney failure. It was demonstrated that all tested amine oxidases, and SSAO to the great extent, play an essential role in the kidney destruction under these conditions [15]. The data formed the basis for the hypothesis on the involvement of the enzyme in the development of other kidney pathologies.…”
mentioning
confidence: 83%
“…Assay for SSAO activity. Fluorometric assay designed earlier [15] was used to estimate activity of the amine oxidase in tissue microsomes and blood. In brief, after preincubation of the enzyme preparations with monoamine oxidase inhibitor pargiline (1×10 -4 M) at room temperature for 20 min, followed by incubation for 30 min at 25°C with substrate (0.1 mM methylamine), the reaction was terminated by addition of 30% ZnSO 4 .…”
Section: Methodsmentioning
confidence: 99%
“…Fluorometric assay was used to estimate activity of all AOs under the investigation (SSAO, DAO, PAO and LOX). The method is based on the formation of an intense fluorophore between folic acid and hydrogen peroxide released during the oxidation of the corresponding amine as a substrate [18,19].…”
Section: Mg/kg)mentioning
confidence: 99%